Verification of the relationship with nature by a quilombola community in Tocantins - Dias Marques, Mauricio [UNESP]; Gois Morales, Angelica [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
The present study aims to verufy how the quilombola community of Lajeado, in Dianopolis, Tocantins, deals with nature or what is its relationship with the natural resources. This study starts with a bibliographic research in search of verified information about the historical aspects of the slavery process in Brazil, the formation of the quilombos and the quilombola communities and the process of the relationship between man and nature over the time. After that, a survey was held for the testimonial and personal experience of a member of the referred community. In a qualitative analysis, reflecting upon the collected data, it is noticed that the tradition, the good habits, preserved throughout generations with care and respect, lead this community to treat the nature with respect, without degrading or defiling it.
Keywords: Slavery process in Brazil; Quilombola community of Lajeado; Relationship with nature; Natural resources; Traditional communities